2013
DOI: 10.4085/1062-6050-48.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Various Methods for Assessing Static Lower Extremity Alignment: Implications for Prospective Risk-Factor Screenings

Abstract: Context: Accurate, efficient, and reliable measurement methods are essential to prospectively identify risk factors for knee injuries in large cohorts.Objective: To determine tester reliability using digital photographs for the measurement of static lower extremity alignment (LEA) and whether values quantified with an electromagnetic motion-tracking system are in agreement with those quantified with clinical methods and digital photographs.Design: Descriptive laboratory study. Setting: Laboratory.Patients or O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
5
19
3
1
Order By: Relevance
“…The results of the present study indicated moderate to excellent inter-and intra-rater reliability for distance variables surrounding the pelvis assessed by the GPS, except for the distance between the PSIS and the midline. These results were consistent with those reported in published studies (19,22,23). A common issue related to the reliability of photographic pelvic posture assessments is the repositioning of markers between measurement sessions.…”
Section: Reliabilitysupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the present study indicated moderate to excellent inter-and intra-rater reliability for distance variables surrounding the pelvis assessed by the GPS, except for the distance between the PSIS and the midline. These results were consistent with those reported in published studies (19,22,23). A common issue related to the reliability of photographic pelvic posture assessments is the repositioning of markers between measurement sessions.…”
Section: Reliabilitysupporting
confidence: 92%
“…For inter-rater reliability, a previous study reported an ICC of 0.43 and an SME of 3.99 on the right and an ICC of 0.49 and an SEM of 4.24 degrees on the left for the pelvic tilt angle. An ICC of 0.84 and an SEM of 2.83 degrees on the right and an ICC of 0.89 and an SEM of 2.16 degrees on the left was reported for the Q angle (23). The smaller SEM values observed in the present study compared with previous studies indicates that the GPS has less measurement error that previous methods when measuring angle parameters.…”
Section: Reliabilitycontrasting
confidence: 56%
See 2 more Smart Citations
“…To date, there is a wide variety of systems that are available for assessments with different levels of reported reliability. Published studies assessing pelvic and lower extremity alignments mostly investigated intra-rater reliability but not interrater reliability [21,24,25]. The Global Postural System (GPS) is a recently developed computerized photographic postural assessment system.…”
Section: Introductionmentioning
confidence: 99%